The Bologna process and the search for excellence: between rhetoric and reality, the emotional reactions of teachers - Bahia, Sara (2018)
There has been an overall change in higher education towards the achievement of outstanding patterns of quality and excellence that assure competitiveness at a global scale. Teachers feel the pressure of official regulations for achieving quality and excellence, based on questionable concepts of quality that do not take into account the experience and beliefs of teachers and lead to emotional states that may promote or hinder adjustment to changes. Thepresent study used a categoricalcontent analysis to capture the emotionsthattwelveuniversityteachersassociatewiththechanges experienced and with the pursuit of quality emphasized in Portugal by the Bologna Process. The results show that participants revealed mixed emotions regarding change. Students elicit mostly positive emotions, whereas bureaucracy, marketization and career changes generate negative emotions that impede the quest for quality, although in a minority of participants they prompt resilience that stimulates engagement in quality.